Experimental research on a 4 K hybrid refrigerator combining GM gas refrigeration effect with magnetic refrigeration effect. (April 2019) - Shen, Jun; Gao, Xinqiang; Li, Ke; Dai, Wei; Li, Zhenxing; Mo, Zhaojun; Zheng, Xinqi; Gong, Maoqiong
Highlights: A hybrid cryogenic refrigerator that combines the magnetic refrigeration effect with GM refrigeration effect was designed. ErNi and TmCuAl were used in the hybrid refrigerator. An optimal phase angle of this hybrid system was figured out. A minimal no-load temperature of 3.5 K was obtained at 0.5 Hz. Abstract: A hybrid cryogenic refrigerator that combines the magnetic refrigeration effect with the GM refrigeration effect has been experimentally studied. ErNi and TmCuAl, which have large magnetocaloric effects, are used to fill the second (low-temperature) stage regenerator of a GM refrigerator and put in a magnetic field varying from 0 to 1.1 T. A phase angle α is defined as the phase between the varying magnetic field and displacer movement and can be tuned in order to find the best timing between the magnetic refrigeration and the GM refrigeration cycle. Efforts have also been made to suppress eddy current losses induced due to the varying magnetic field through the cold head. A phase angle of 60° was found to generate best cooling performance through experiments. A minimal no-load temperature of 3.5 K was obtained at 0.5 Hz while the GM refrigeration alone can only generate a no-load temperature of 4.2 K.